Dinamika Penggunaan Busana Adat ke Pura di Karangasem - Wayan Yanik Yasmini (Lembaga Penjaminan Mutu STKIP Agama Hindu Amlapura, 2022)
This qualitative study aims to describe the form of traditional clothing, the dynamics of traditional clothing, and the factors that influence the dynamics of using traditional clothing to the temple. This research approach is an empirical approach. Methods of data collection using interviews, document recording, and observation. This type of research data is qualitative data, which comes from primary and secondary sources. The data is processed by induction and argumentation techniques. Based on the results of data analysis, it can be concluded that (1) the traditional clothing to the temple used by the Karangasem community is distinguished according to the gender of the user, namely men's traditional clothing and women's traditional clothing. (2) The use of special clothing for men, namely wearing clothes, using cloth (kamben), scarf, headdress/udeng, shawl (senteng/ubed-ubed/slempot), while for women using kebaya kamen. scarf/senteng. Here, many people who experience the dynamics of dressing do